The Effectiveness of Acupressure and Slow Deep Breathing (SDB) Toward Peak Expiration Current Value in Asthma Patients - Ferry Fadli Fratama (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Asthma has affected more than 5% of the population around the world which causes mortality problems and asthma morbidity tends to increase. The presence of asthma indicators can be seen from the decreased lung function value or the clinical picture results in the classification of persistent weight i.e. the peak expiratory current value is less than 60% and the peak expiratory current variability value is more than 30%. One of the treatment of asthma with traditional health services which is a national cultural heritage that has been growing and developing in Indonesia, one of which is massage. Types of massage that are developing at this time include acupressure. Acupressure is a simple, easy to do complementary (non-pharmacological) therapy that has no side effects because it is not an invasive action. Besides acupressure, therapy slow deep breathing (SDB) can also help and reduce asthma sufferers in Indonesia. Methods This research is a Quasy Experimental with a pre-test – post-test with control group design. This research arranged two groups namely the intervention group that was given acupressure therapy at the acupoint points of Tiantu (CV 22), Lieque (LU 7) and Taiyuan (LU 9) with slow deep breathing (SDB), while the control group was only given therapy slow deep breathing (SDB) without acupressure. Technique Probability sampling with purposive sampling method is used to get 36 respondents who are divided into 2 groups. Results Test results Repeated Measure Anova showed a significant difference with p value 0.000 (<0.05) means that the intervention group is better at increasing peak expiratory current than the control group. Conclusion Acupressure and slow deep breathing (SDB) therapy for 14 days with 2 measurements was very effective in increasing peak expiratory current.